Entangling the ro-vibrational modes of a macroscopic mirror using radiation pressure - Bhattacharya, M; Giscard, P; Meystre, P (Optical Society of America, 2008)
We explore the ability of radiation pressure to entangle macroscopic objects, using a Laguerre-Gaussian mode in a cavity containing a mirror that can vibrate as well as rotate. © 2008 Optical Society of America.